Legal Analysis of Issues of Evidence and Testimony in Civil Disputes in Court - Mohammad Salwa Zakky; Azriel Asshidiqi; Anggi Sri Hayati Simarmata (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to conduct a legal analysis of issues related to evidence and testimony in civil disputes in court, with a focus on the interaction between legal norms and judicial practice. The method used is normative legal research employing a legislative, conceptual, and case-based approach, analyzed through systematic, grammatical, and teleological legal interpretation. The results of the study indicate that the system of evidence in Indonesian civil procedure law still relies on classical principles such as actori incumbit probatio, vrij bewijsstelsel, and unus testis nullus testis; however, its implementation faces challenges in the form of inconsistencies in the evaluation of evidence, limitations on the probative value of witness testimony, and the suboptimal recognition of electronic evidence. Advances in information technology have also spurred the emergence of new forms of evidence that have not yet been fully and systematically accommodated within civil procedure law. This study proposes a normative reconstruction through the strengthening of regulations, the integration of electronic evidence, and the enhancement of the judge’s role in evaluating evidence objectively and rationally. The contribution of this research lies in the development of a more adaptive conceptual framework for evidence that responds to the dynamics of modern law, thereby enhancing legal certainty and justice in the resolution of civil disputes.